Benznidazole/Poloxamer 407 Solid Dispersion as a New Strategy to Improve the Treatment of Experimental Trypanosoma cruzi Infection - Devies, Carolina; Simonazzi, Analía; Micheloud, Juan Francisco; Ragone, Paula Gabriela; Cid, Alicia Graciela; Sánchez Negrette, Olga; Bermúdez, José María; Parada, Luis Antonio (American Society of Parasitologists, 2024)
Benznidazole and nifurtimox are the only drugs specifically approved for the treatment of Chagas disease. Both compounds are given orally in tablets, but occasionally are ineffective and cause adverse effects. Benznidazole, the first-line treatment in many countries, is a compound with low solubility in water that is administered at high doses for long periods of time. To improve its solubility, we developed a new liquid formulation on the basis of solid dispersions (SD) using the amphiphilic polymer poloxamer 407. Herein we present data on its trypanocidal performance in mouse models of acute and chronic Trypanosoma cruzi infection. SD at doses of 60 or 15 mg/kg per day given with different administration schedules were compared with the commercial formulation (CF; 50 mg/kg per day) and vehicle. The SD performance was assessed by direct parasitemia, total anti-T. cruzi antibodies, and parasitic burden in tissues after 4 or 6 mo posttreatment. The efficacy of the SD was equivalent to the CF but without manifest side effects and hepatotoxicity. Considering our previous data on solubility, together with these on efficacy, this new liquid formulation represents a promising alternative for the treatment of Chagas disease, particularly in cases when dosing poses a challenge, as in infants.